2017
DOI: 10.1111/ilr.12016
|View full text |Cite
|
Sign up to set email alerts
|

Six central features of the Chinese labour market: A literature survey

Abstract: In this comprehensive analytical overview, the author pays particular attention to the changing structure of China's employment towards more private‐sector jobs in urban areas; its rising wages and widening earnings inequality; the persistence of its hukou system, causing labour market discrimination, an urban labour shortage and a rural labour surplus; its more market‐oriented wage structure, albeit with segmentation between firm ownership types; its relatively low unemployment; and the relatively weak role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 69 publications
0
22
0
Order By: Relevance
“…Overtime work among the migrant workers group reflects the current segmentation of the Chinese labor market. Studies have shown that employment discrimination based on “hukou” is more serious, and it is also the main reason for the division of the urban labor market (118). Therefore, reform of the household registration system should be the main focus of attention in order to eliminate labor market segmentation and promote integration of the labor market, which would lead to a break away from the institutional separation of the market and a shift toward the establishment of a unified labor market in which labor can flow freely.…”
Section: Resultsmentioning
confidence: 99%
“…Overtime work among the migrant workers group reflects the current segmentation of the Chinese labor market. Studies have shown that employment discrimination based on “hukou” is more serious, and it is also the main reason for the division of the urban labor market (118). Therefore, reform of the household registration system should be the main focus of attention in order to eliminate labor market segmentation and promote integration of the labor market, which would lead to a break away from the institutional separation of the market and a shift toward the establishment of a unified labor market in which labor can flow freely.…”
Section: Resultsmentioning
confidence: 99%
“…The current situation is thus more complex than the mere depletion of the available rural workforce. Labour shortages in the most industrialised areas of coastal provinces are combined with a persistent rural workforce surplus (approximately 110m workers) ready to accept very low wages, but no longer attracted by the low benefits of migration (Song, 2017).…”
Section: Wages In China: a Kuznets–lewis Textbook Case?mentioning
confidence: 99%
“…The power imbalance in the wage relationship nonetheless persists due to the inability of the trade union to truly defend the rights of the mingong within factories. According to Song (2017), the presence of the ACFTU in companies does not have a positive effect on wages. 7 The lack of legitimate workers’ representatives contributes to the high level of conflicts in China.…”
Section: A ‘Chinese-style’ Industrial Relations Systemmentioning
confidence: 99%
“…Our analysis of rent sharing in China is also of particular interest given the country's particular institutional structure. Despite its impressive economic growth over the last decades, many formal labour market institutions that are common in OECD countries are at a much earlier stage of development in China (Song, 2017). These institutions include collective bargaining, independent trade unions, and employment protection law, as well as unemployment benefits and other forms of social protection.…”
Section: Introductionmentioning
confidence: 99%